Effectiveness of a Local Wisdom–Based Spiritual Intervention on Work Happiness and Caring Behavior among Nurses: A Randomized Mixed-Methods - Nur, Kholid Rosyidi Muhammad; Asmaningrum, Nurfika; Wijaya, Dodi; Kurniawan, Dicky Endrian; Rondhianto, Rondhianto (Journal of Applied Nursing and Health, 2026)
Background: Nurses often face high job demands and emotional stress that may reduce work happiness and caring behavior. Previous studies have examined workplace well-being interventions; however, culturally grounded spiritual programs integrating local wisdom remain insufficiently tested using rigorous experimental designs, particularly in low- and middle-income countries (LMICs). This study aimed to evaluate the effectiveness of a local wisdom–based spiritual program in improving work happiness and caring behavior among inpatient nurses in Indonesia. Methods: A mixed-methods randomized controlled trial following CONSORT guidelines was conducted with 120 inpatient nurses at two hospitals in Jember, Indonesia. Eligible nurses (>1-year inpatient experience) were randomly assigned to either an intervention group (n = 60) or a control group (n = 60). The intervention group participated in a 12-week spiritual program (Pengajian and Tari Molong Kopi) that included routine activities. The independent variable was program participation, and the dependent variables were work happiness and caring behavior measured using the Oxford Happiness Questionnaire (OHQ) and Caring Behavior Inventory (CBI) at baseline, week 6, and week 12. Data were analyzed using repeated-measures ANOVA, effect sizes (Cohen’s d), correlation, and 95% confidence intervals. Qualitative responses were analyzed thematically. Results: Participants were mostly female (87%) with a mean age of 32 years. The intervention group showed significantly greater improvements in OHQ and CBI scores at weeks 6 and 12 compared with controls (p < 0.001), with moderate-to-large effects (d = 0.65–0.82). Work happiness correlated with caring behavior (r = 0.52). Themes included enhanced mindfulness, emotional release, renewed professional meaning, and stronger collegial relationships. Conclusion: Local wisdom–based spiritual programs significantly enhance nurses’ work happiness and caring behavior. Integrating culturally grounded spiritual practices into workplace well-being initiatives may strengthen the quality of nursing care in LMIC hospital settings.